The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.3758/bf03197281
|View full text |Cite
|
Sign up to set email alerts
|

Attention and implicit memory tests: The effects of varying attentional load on conceptual priming

Abstract: The role of attention during encoding is important to many current accounts of the implicit/explicit memory distinction. Some accounts suggest that implicit memory tests reflect automatic (non-attentiondemanding) encoding processes, whereas other accounts (such as the transfer-appropriate-processing view) suggest that performance on conceptual implicit tests requires attention during encoding. The present study manipulates attention at encoding over several levels (by varying short-term memory load) and examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
143
8

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(170 citation statements)
references
References 52 publications
19
143
8
Order By: Relevance
“…By this logic, dividing attention should limit semantic processing during encoding and should have deleterious effects on conceptual priming. Indeed, that is what we have found for exemplar generation, and what has been found by previous investigators ofthis task who have varied level of encoding or who have used sufficiently demanding distractor activities during encoding (e.g., Gabrieli et aI., 1995;Hamann, 1990;Maki & Knopman, 1996;Monti et aI., 1996;Mulligan, 1997;Mulligan & Hartman, 1996). By contrast, in the present experiments, neither reduced level ofprocessing nor division ofattention has produced reliable deficits in priming in category verification.…”
Section: Conceptual Primingcontrasting
confidence: 55%
See 3 more Smart Citations
“…By this logic, dividing attention should limit semantic processing during encoding and should have deleterious effects on conceptual priming. Indeed, that is what we have found for exemplar generation, and what has been found by previous investigators ofthis task who have varied level of encoding or who have used sufficiently demanding distractor activities during encoding (e.g., Gabrieli et aI., 1995;Hamann, 1990;Maki & Knopman, 1996;Monti et aI., 1996;Mulligan, 1997;Mulligan & Hartman, 1996). By contrast, in the present experiments, neither reduced level ofprocessing nor division ofattention has produced reliable deficits in priming in category verification.…”
Section: Conceptual Primingcontrasting
confidence: 55%
“…Here too, the results have been inconsistent. Some studies report that dividing attention reduces priming in exemplar generation (Gabrieli et aI., 1995;Gabrieli et aI., 1999;Mulligan, 1997;Mulligan & Hartman, 1996), whereas others do not (Isingrini, Vazou, & Leroy, 1995;Schmitter-Edgecombe, 1996). Although Koriat and Feuerstein (\ 976) found a null effect of dividing attention on priming in word association, another task that involves access to semantic information, Mulligan (1998) reported that digit monitoring reduced priming in this task.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, participants are more likely to correctly answer general knowledge questions if they were exposed to the answer in an unrelated learning phase (e.g., Blaxton, 1989;Challis & Sidhu, 1993;Hamilton & Rajaram, 2001). Similarly, participants are more likely to incorporate a critical exemplar (typically of low frequency; e.g., cheetah) during a category instance generation task (e.g., list the first eight animals that come to mind; see Geraci & Rajaram, 2004;McDermott & Roediger, 1996;Mulligan, 1997;Rappold & Hashtroudi, 1991;Srinivas & Roediger, 1990) if they have been previously exposed to that item.…”
Section: Szpunarmentioning
confidence: 99%